Assessment of Platelet Count in Pediatric Patients with Dengue Fever Admitted in A Tertiary Care Hospital of Bangladesh - Datta, Mitra; Ferdousi, Asma; Ahmed, Farid Uddin; Barua, Dazy; Biswas, Susmita; Amin, Jabed Bin; Samad, Rasheda (IAHS Medical Journal, 2022)
Background: Dengue is a major vector-borne disease that is prevalent in tropical and sub-tropical countries. A hallmark of dengue fever is thrombocytopenia. This study was conducted to evaluate the platelet count in relation to severity and outcome of dengue infection in a cohort of hospitalized children during 2019 dengue outbreak in Bangladesh. Materials and methods: This observational study was carried out in the Department of Pediatrics of Chittagong Medical College Hospital, Chattogram, Bangladesh. One hundred and ninety two consecutive serologically positive dengue cases (Age £ 12 years) admitted from July 2019 to December 2019 were enrolled in the study. Platelet count was done daily from day 3 to 7 days of illness. Results: Overall the mean age was 7.04 (±3.23) years with male preponderance (59.4%). As per the nadir platelet count 53 (27.7%) patients had counts >150,000, 66 patients (34.3%) had count between 100,000 and 150,000, 36 patients (18.7) had count between 50,000 and 1, 00,000, 13 patients (15.1%) had count between 20,000 and 50,000 while the remaining 6 patients (3.1%) had profound thrombocytopenia. Children with profound thrombocytopenia were likely to had dengue shock syndrome and prolonged hospitalization. There was no fatality in this series. Conclusion: Though thrombocytopenia was common profound thrombocytopenia was not frequent in the hospitalized pediatric patients with dengue infection. IAHS Medical Journal Vol 4(1), June 2021; 13-16